Carbon Sequestration under an Agri-silvicultural System in the Arid Region - Singh, Genda (Indian Forester, 2005)
Soils of the dry regions have low capacity to sequester carbon. The large extent of such areas may be important in its potential to sequester more carbon and act as carbon sink. An eight-year study was carried out on soil organic carbon dynamics and was related with three years litter dynamics study in Emblica officinalis, Hardwickia binata and Colophospermum mopane based agroforestry systems. Half of the area was cultivated under fixed crop of Vigna radiata and the other half under rotational crop oflegume rotated by non-legume. In addition, there was a control plot under tillage. Soil carbon content decreased with time in control plot with a loss of SOC by 56% during the study period. However, integration of trees allowed a loss of SOC only by 3.2% in E. officinalis, 22% in H. binata and 35.5% in C. mopane plots, indicating greater sequestration of carbon in E. officinalis plot and least in C. mopane plot. The study suggests that integration of tree in agricultural land is an important strategy to sequester carbon not only in the form of biomass but also in soil and may therefore maintain soil productivity.